Optimal Design of Elastic Circular Plane Arches - Francesco Trentadue; Alessandra Fiore; Rita Greco; Giuseppe C. Marano; Nikos D. Lagaros (Frontiers in Built Environment, 2020)
Arches represent a structural system adopted in construction practice for thousand years, and they are still widely adopted if large spans have to be covered. The structural efficiency of arches principally depends on the minimization of the eccentricity of the pressure curve, which allow us to reduce their structural weight. Despite the millenarian use and a very abundant literature, there is still scope for design optimization of arches. This study is framed within this context and is focused on plane circular arches under uniformly distributed vertical load and self-weight. The arches are elastically clamped at both end sections. A semianalytical approach is developed to minimize the volume, with the aim of determining the fundamental mechanical parameters governing the optimal design. Finally, the results are charted to allow their use in a design process.